2017
DOI: 10.18632/oncotarget.14870
|View full text |Cite
|
Sign up to set email alerts
|

Association of VEGFA polymorphisms with susceptibility and clinical outcome of hepatocellular carcinoma in a Chinese Han population

Abstract: Vascular endothelial growth factor A (VEGFA) is an important angiogenesis regulator, which plays an important role in angiogenesis and progression of tumor, including hepatocellular carcinoma (HCC). We aimed at determining whether single nucleotide polymorphisms of VEGFA gene influence the development and clinical outcomes of HCC. We analyzed four potential functional polymorphisms (936C/T, 634G/C, 1612G/A, 2578C/A) of VEGFA gene in 476 HCC patients and 526 controls using matrix-assisted laser desorption ioniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Different studies showed that associations were variables and differed according to tumor type. Data from case‐control studies revealed similar results with cervical cancer (OR (95% CI), 0.39 (0.16‐0.96), P = .040), prostate cancer (OR (95% CI), 0.16 (0.04‐0.70), P = .007) and hepatocellular carcinoma (OR (95% CI), 0.51 (0.28, 0.92), P = .024) . Mishra et al also found that CA genotype was associated with decreased risk of Gallbladder cancer risk.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Different studies showed that associations were variables and differed according to tumor type. Data from case‐control studies revealed similar results with cervical cancer (OR (95% CI), 0.39 (0.16‐0.96), P = .040), prostate cancer (OR (95% CI), 0.16 (0.04‐0.70), P = .007) and hepatocellular carcinoma (OR (95% CI), 0.51 (0.28, 0.92), P = .024) . Mishra et al also found that CA genotype was associated with decreased risk of Gallbladder cancer risk.…”
Section: Discussionmentioning
confidence: 74%
“…Data from case-control studies revealed similar results with cervical cancer (OR (95% CI), 0.39 (0.16-0.96), P = .040), 16 prostate cancer (OR (95% CI), 0.16 (0.04-0.70), P = .007) 17 and hepatocellular carcinoma (OR (95% CI), 0.51 (0.28, 0.92), P = .024). 18 Mishra et al 19 also found that CA genotype was associated with decreased risk of Gallbladder cancer risk. In another case-control study, a significant association was observed with carriers of CC genotype in patients with increased nasopharyngeal cancer risk in Tunisian 20 and with invasive breast cancer in an American cohort (OR (95% CI), 1.46 (1.00-2.14), P = .049).…”
Section: Discussionmentioning
confidence: 97%
“…Upregulated VEGFA is common in many tumors and is related to tumor stage and progression. Liu et al 64 reported that VEGFA polymorphisms might play a potential role in the development and clinical outcome of hepatocellular carcinoma. VEGFA has also been found to be inhibited by miR-1, which exerts inhibitory functions in osteosarcoma cells, as well as promotes proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF), one of the most prominent regulators involving vasculogenesis, is highly expressed in human HCC specimens (Choi et al, 2017;Liu et al, 2017). Hypoxia is one of the most potent stimuli for increased VEGF production in tumor cells (Liu et al, 2017;Campbell et al, 2019). With tumor tissues growing, one of the critical mediators of hypoxic responses is the hypoxia-inducible factor 1a (HIF-1a).…”
Section: Introductionmentioning
confidence: 99%